ANALYSIS OF CLIMATE COMFORT LEVEL IN JAM GADANG TOURISM AREA - Purnama, Fahmi yuwan; M, Nurul Hasanah; Miokta, Thedy Gio; Raymon, M. Fatahilah; Virgianto, Rista Hernandi (Jurnal Segara, 2024)
The potential of the tourism sector is very important, especially in terms of economic development. One of the factors affecting the tourism sector is the comfort of climatic conditions. Information about climatic conditions becomes the main factor in choosing the destination of a tourist trip. This study aims to analyze the level of climate comfort in the Jam Gadang tourist area of West Sumatra Province based on the Temperature Humidity Index (THI), Discomfort Index (DI), and Humidex Index. The use of secondary data from the parameters of air temperature and daily air humidity obtained from the Bukit Kototabang Global Atmospheric Monitoring Station with a period range of 2010-2020. Processing using R-Studio and Microsoft Excel software. The method used is descriptive analysis. The results showed that the level of climate comfort in the jam gadang tourist area based on the THI, DI, and Humidex indices was included in the comfort category. May is the month with the highest level of comfort. then November is the month with the lowest level of comfort. All three indices have positive correlation values. The influence of the IOD phenomenon when neutral conditions, DM+, and DM- as a whole shows that the index value categories THI, DI, humidex belong to the comfort category. However, humidex index values when DM+ and DM- conditions fall into the category are a little uncomfortable. The average value of the THI index when it is neutral is 20.8 ºC, while at the time of DMI+ and DMI- the average index is the same at 21.7 ºC. Then, the average index value of DI when neutral conditions is 20.9 ºC, while when conditions are DMI+ and DMI- the average is 21.7 ºC. Then, the average value of the humidex index when the neutral condition is 28.1 ºC. While at the time of DMI+ and DMI- the average index is the same at 29.5 ºC.